“Single, seventies, and stuck”: a discourse analysis of the “leftover women” or Sheng Nu in China in the blogosphere - Murti, Desideria Cempaka Wijaya (Penerbit Universiti Kebangsaan Malaysia, 2019)
The government of China introduced the lexicon of “leftover women,” or sheng nu, to publicly signify the “eligible but unmarried women between age 27 to 35” in 2010. Although it was a derogatory lexicon against women, but some researchers have argued that sheng nu is a sign of women’s emancipation because these women usually have successful careers. The diverse perceptions in Chinese society about the issue of “leftover women” have become a thought-provoking subject for investigating the debate on positive and negative framing of women and continue to assess the unexplored gender perspective on the discursive construction of women in China through the pervasive growth of digital media. This research examined the blogosphere related to the issue of leftover women in China in order to understand how the blogger negotiate the meaning of sheng nu in the digital community. This study provided insight to explore the discursive construction of women in China by investigating the dynamics of the depiction of unmarried women. The discourse analysis was chosen to answer the main research question on how the bloggers negotiate the meaning of sheng nu, or the leftover women, in China using blogs as a platform of resistance. As a result, the blogger evaluated the sheng nu as the dilemmatic problem of the A-class of women. Also, upon the hegemonic power to suppress women, the bloggers can potentially identify the conflict and negotiate the issue of leftover women under a system of knowledge by shifting the meaning of sheng nu and by using the freedom of creation in the blog.